Tecnologia assistiva no ensino de Matemática para um aluno cego do Ensino Fundamental: Desafios e possibilidades - Salvino, Ligiane Gomes Marinho (2017)
The teaching of mathematics aimed at students with special educational needs, students with or without disabilities, that responds to such needs is the precondition of inclusive mathematical education. Thus, the main objective of the present study was to investigate the use of assistive technology resources in mathematics teaching for a student with acquired blindness enrolled in elementary school, in a public school located in the backcountry of Paraíba. To do so, we use a qualitative approach, following the design and methodological rigor of a case study. This research analyzed the difficulties of the blind student, observed the practices of the mathematics teacher and the teacher of the Specialized Educational Assistance - AEE and created products of assistive technology that can mediate the processes of teaching and learning the mathematical contents with blind students. Data were collected through interviews, direct observations and participant observations, with didactic interventions aimed at an inclusive mathematics teaching. The discussion of the data was based on the technique of content analysis, from which three categories emerged: Human Resource Capacitation and Material Resource Acquisition: Is José educational inclusion guaranteed?; Pseudo-inclusion: denial of José's deficiency; José and mathematics: a possible relationship. The first category discussed the importance of teacher training and the support of accessible learning materials; The second category presents the mistaken actions that deny José's deficiency. Finally, the third category addresses the products created and applied in José's mathematics teaching. The results pointed out that although teacher training and the availability of accessible didactic materials are essential, inclusion requires the will, the intention, the desire to do different. Denial comes from exclusive practices deriving from lack of training, but also from lack of interest and initiative. Finally, it was verified that the Braille reading and writing process; The soroban and the digital technologies are indispensable for the effectiveness of the process of teaching and learning of the mathematical contents.